500 Years of Christianity and the Global Filipino/a - Lledo Gomez, Cristina,Brazal, Agnes M.,Ibita, Ma. Marilou S. (Springer Nature Switzerland, 2024)
1 Philippine Christianity: 500 Years of Resistance and Accommodation – 2 Indigenization as Appropriation (What Being Baptized Could Have Meant for the Natives of Cebu in 1521) – 3 The Double Truth of (Colonial) Mission – 4 Rethinking Encounters and Re-imagining Muslim-Christian Relations in Post-colonial Philippines – 5 The Glocal Filipins and the Pasyon Through the Lens of Ethnicity – 6 An Independent Catholic, Nationalist People’s Movement: The Iglesia Filipina Independiente (Philippine Independent Church) – 7 Philippine, Independent and International: The Relationship Between—the Iglesia Filipina Independiente and the Old Catholic Churches – 8 Indigenous Inculturation: A Hermeneutics of Serendipity – 9 Decolonizing the Diaspora through the Center for Babaylan Studies – 10 Back from the Crocodile’s Belly: Christian Formation Meets Indigenous Resurrection Redux – 11 The Ygollotes’ Pudong and the Insurrection of the Reeds In the Post-Human Commune – 12 Introducing Jeepney Hermeneutics: Reading the Bible as Canaanites – 13 Inang Diyos, Inang Bayan: The Virgin Mary and Filipino Identity – 14 Bangon Na, Pinays Rise Up: Reclaiming Pinay Power Dismantled by a Christian Colonial Past and Present – 15 Re-Baptizing Spirit in Land and Ancestry: An Approach for Un-Doing Christian Colonialism – 16 Toward Reclaiming the Wisdom of our Forebears: Nature and Environment from a Filipino Perspective. The year 2021 marked the five-hundredth anniversary of Christianity in the Philippines. With over 90% of the Filipin@s (Filipino/as) in the country and more than eight million around the world identifying as Christian, they are a significant force reshaping global Christianity. The fifth centenary called for celebration, reflection, and critique. This book represents the voices of theologians in the Philippines, the United States, Australia, and around the world examining Christianity in the Philippines through a postcolonial theological lens that suggests the desire to go beyond the colonial in all its contemporary manifestations. Part 1, “Rethinking the Encounters,” focuses on introducing the context of Christianity’s arrival in the archipelago and its effect on its peoples. Part 2, “Reappropriation, Resistance, and Decolonization,” grapples with the enduring presence of coloniality in Filipinreligious practices. It also celebrates the ways Christianity has been critically and creatively reimagined. Cristina Lledo Gomez is the Presentation Sisters Lecturer at BBI-The Australian Institute of Theological Education (BBI-TAITE) and a Research Fellow for the Australian Centre for Christianity and Culture, Charles Sturt University, Australia. Her role at BBI-TAITE is directed toward promoting women’s spiritualities, feminist theologies, and ecotheologies. Agnes M. Brazal is a Full Professor in the Department of Theology and Religious Education at De La Salle University Manila, The Philippines, former President of DaKaTeo (Catholic Theological Society of the Philippines), and author/editor of eleven books that include A Theology of Southeast Asia: Liberation-Postcolonial Ethics in the Philippines (2019). Ma. Marilou S. Ibita is an Associate Professor in the Department of Theology and Religious Education at De La Salle University, The Philippines, and a Visiting Professor in the Faculty of Theology and Religious Studies at the Katholieke Universiteit Leuven, Belgium. Her research centers around biblical literature and Jewish-Christian dialogue.
10.1007/978-3-031-47500-9
Keywords: Aufsatzsammlung; Theology.; Religions.; East Asia.; Religion; Ethnology; Culture.; Southeast Asia; Asian history; Asiatische Geschichte; Christentum; Christian theology; Christianity; Cultural studies; Geschichte der Religion; HISTORY / Asia / Southeast Asia; History of religion; Kulturwissenschaften; Oriental religions; Ostasiatische Religionen; RELIGION / Christian Theology / General; RELIGION / Christianity / General; RELIGION / Christianity / History; RELIGION / Eastern; SOCIAL SCIENCE / Anthropology / Cultural; Theologie